2010
DOI: 10.1073/pnas.1004279107
|View full text |Cite
|
Sign up to set email alerts
|

The apical transmembrane protein Crumbs functions as a tumor suppressor that regulates Hippo signaling by binding to Expanded

Abstract: The Hippo signaling pathway regulates organ size and tissue homeostasis from Drosophila to mammals. At the core of the Hippo pathway is a kinase cascade extending from the Hippo (Hpo) tumor suppressor to the Yorkie (Yki) oncoprotein. The Hippo kinase cascade, in turn, is regulated by apical membrane-associated proteins such as the FERM domain proteins Merlin and Expanded (Ex), and the WW- and C2-domain protein Kibra. How these apical proteins are themselves regulated remains poorly unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
359
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(378 citation statements)
references
References 33 publications
16
359
3
Order By: Relevance
“…et al, 2010. Furthermore, as an upstream component of Ex, the transmembrane protein Crumbs (Crb), a determinant of epithelial apical-basal polarity in Drosophila embryos, was also identified (Ling et al, 2010). These new factors are likely to function as apical components of the WrsHpo signaling pathway.…”
Section: Regulation Of Growth Through the Wts-hpo Signaling Pathwaymentioning
confidence: 99%
“…et al, 2010. Furthermore, as an upstream component of Ex, the transmembrane protein Crumbs (Crb), a determinant of epithelial apical-basal polarity in Drosophila embryos, was also identified (Ling et al, 2010). These new factors are likely to function as apical components of the WrsHpo signaling pathway.…”
Section: Regulation Of Growth Through the Wts-hpo Signaling Pathwaymentioning
confidence: 99%
“…A number of cell polarity and cell adhesion proteins were also found to regulate the Hippo pathway. These include the Scribble (Scrib)-Discs large (Dlg)-Lethal giant larvae (Lgl) complex, atypical protein kinase C (aPKC), Crumbs (Crb) , and Echinoid (Ed) (Chen et al, 2010a;Grzeschik et al, 2010;Ling et al, 2010;Robinson et al, 2010;Yue et al, 2012), indicating a role of cell polarity and cell adhesion in Hippo pathway regulation. Furthermore, two studies identified Tao-1, a STE20 family protein kinase as a positive regulator of the Hippo pathway, possibly by directly phosphorylating and activating the Hpo kinase (Boggiano et al, 2011;Poon et al, 2011).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
“…The Ex-Mer-Kibra complex or subcomplexes may activate Hpo-Sav through direct interactions. The atypical cadherin Fat (Ft) and the apical transmembrane protein Crumbs (Crb) function as tumor suppressors and have been implicated as potential cell surface receptors for Hippo signaling (Grzeschik et al, 2010;Ling et al, 2010;Robinson et al, 2010). Crb and Ex directly bind to each other, linking a transmembrane protein to an apical component of the Hippo pathway.…”
Section: Overview Of the Hippo Pathwaymentioning
confidence: 99%